Evaluasi Tingkat Aktivitas Fisik Harian Siswa selama Pembelajaran PJOK Daring dan Luring - Fatoni; Anwar, Nur Indah Atifah; Alimsyah, Andi Saiful; Alim, Bahrul; Raswadi, Mohammad Dika (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to evaluate and compare the level of daily physical activity of students during online and offline Physical Education, Sports, and Health (PJOK) learning at SMA Negeri 2 Sinjai. The approach used is quantitative with a descriptive comparative design. The sample consisted of 60 students selected purposively, 30 students each from the online and offline learning groups. Data were collected through a physical activity questionnaire modified from the PAQ-A instrument and analyzed using an unpaired t-test. The results showed that there was a significant difference between the two groups, where students in offline learning had a higher average physical activity score (3.45) compared to students in online learning (2.68), with a p value = 0.002. These findings indicate that offline PJOK learning is more effective in increasing students' daily physical activity. This study recommends the development of adaptive PJOK learning strategies so that students remain physically active, especially in distance learning situations.